THE INTEGRATION OF THE PREDICT-OBSERVE-EXPLAIN (POE) MODEL WITH A DEEP LEARNING APPROACH IN TEACHING SCIENCE - Herolika, Felling; Ahmala, Majidatun (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2025)
Science learning in elementary school requires an approach that helps students develop a deep and meaningful understanding. This study aims to investigate the effectiveness of integrating the Predict-Observe-Explain (POE) learning model with a deep learning approach in improving the learning outcomes of fourth-grade students at SD Negeri 9 Pendopo Barat. The research used experimental method and one group pretest-postest design. The participants were 28 students, consisting of 14 girls and 14 boys. Data were collected through a pre-test before the intervention and a posttest afterward. The pre-test results showed an average score of 62.07, with 42.86% of students meeting the minimum learning criteria. After the learning activities, the average post-test score increased to 77.46, with 89.29% of students achieving mastery. This improvement suggests a positive impact from using the POE model combined with the Deep Learning approach, which includes mindful, meaningful, and joyful learning. These results indicate that the strategy effectively enhances learning outcomes and encourages active student engagement in science lessons. Therefore, this approach is recommended for science education at the elementary level.